Microcrédito emancipatório no nordeste do Brasil? : estudo de caso do Crediamigo Comunidade nos municípios de Caucaia-Ce e Maranguape-Ce - Bandeira, Carlos Idelfo Araújo (2008)
This piece of work consists in a study case of Crediamigo Comunidade, a product from the portfolio of Crediamigo Program of Banco do Nordeste, that uses the methodology of the Comunitary Banks in the concession of low amount loan to poor communities. The main question consists to understand how the Crediamigo Comunidade is characterized faced to the conflict of emancipatory versus liberal paradigms, that exists in the microcredit area. The main objective will analyze how the mechanisms: social capital, empowerment, formation to credit education and better conditions for economic and social issues promoted in the specific objectives of this product, before the dipute between these paradigms. The method adopted analyzed, in a longitudinal perspective, the three years of the product s existence (jun/2005 to jul 2008). Primary and secondary data made possible to identify qualitatively, emancipatory and non emancipatory attributes in the actions and results of Crediamigo Comunidade. It is concluded that the Crediamigo Comunidade works in a liberal logic of the Crediamigo Program, consequently, his focus is not in the emancipation of the poorest clients. The empowerment is individual and not communitary or Freiriano ; the social capital relations enlarges itself in its bounding and bridging ties, but not in its linkage ties, to have access to politic actors and consequently communitary strengthen. All the formation in the Crediamigo is strictly commercial. These characteristics happen by the liberal paradigm in the Crediamigo management and of all of its products, including the Crediamigo Comunidade